PELATIHAN KEYBOARDING SKILL BAGI GURU SMK MUHAMMADIYAH 2 TELOGOMAS KECAMATAN LOWOKWARU KOTA MALANG - Diana Eka Poernamawati; Achmad Zaini; Tri Wahyu Widodo; Achmad Suyono; Tatiana Kristianingsih (Publisher UPT P2M Politeknik Negeri Malang, 2019)
Typing with the blind 10 finger technique is one of the competencies that must be possessed by vocational students. Achieving this competency is not easy, to further support the efforts of the teachers in facilitating the implementation of their work it would need support from various parties. Malang State Polytechnic as part of the community, which is a higher education institution, with one of its tasks is to improve the quality of human resources through the Community Service pathway obliged to provide guidance assistance to teachers of Malang Muhammadiyah 2 Vocational School about key boarding technique teaching methods using the application.Technological advances allow teaching that is more fun and not boring. One of the technologies that can be applied to keyboarding subject teaching is to use the Typing Master Pro application. It is expected that the varied teaching methods will facilitate the achievement of the competencies needed by students.